Deslocamentos do feminino e do amor - Marcela Oliveira (O Que Nos Faz Pensar)
This article presents displacements of the idea of ​​“feminine” in relation to configurations of “love” in the history of literature. The construction of a feminine identity, which with different nuances permeates the western tradition, will be seen in the origin of poetry, in Homer; and in three modern expressions that reveal the passing aspect of the new times: Baudelaire’s Passant, Flaubert’s Emma Bovary and Proust’s Albertine. In these characters, one can notice traces of ambiguity around their appearance and intentions, which are shown in the way they move, or lead others to move, in love encounters.